Analisis Dampak Corporate Governance terhadap Tax avoidance Pada Perusahaan Pertambangan Listed di Bursa Efek Indonesia (BEI) - Eka Mya Auddina (Department of Islamic Economic Law, Institut Agama Islam (IAI) Al-Qolam, 2018)
This research is intended to analyze the influence of corporate governance towards tax avoidance. The method of research is descriptive quantitative. The type of data in this study using secondary data sourced from the company's annual report which is accessible through www.idx.co.id. The population in this research is the mining company listed on the Indonesia stock exchange totaling 41 companies with some specific criteria so as to generate a sample of research a number of 10 companies. The data analysis techniques used to influence corporate governance against tax avoidance is the data panel. Variables used in measuring corporate governance is the composition of the Board of Commissioners are independent, the composition of the audit committee, and the managerial ownership. The results of this study is that the Board of Commissioners of the independent variables are declared to tax avoidance. Furthermore, the audit Committee stated variable effect on tax avoidance. Managerial ownership variables are declared to have no effect against tax avoidance. While Ssimultaneously, corporate governance is declared to tax avoidance. Based on research results, there are still some companies that they do tax avoidance by using measurements of the current etr. Then the management of the company is expected to pay more attention to any action or decision taken with regard to corporate taxes. While the Government is expected to be more rigorous in supervising the company in order for the payment of taxes in accordance with the tax burden thus spared from losses arising from the payment of taxes is not optimal.